A novel risk-based decision-making paradigm - Morgado, Pedro; Marques, Fernanda; Silva, Miguel B.; Sousa, Nuno; Cerqueira, João J. (Frontiers in Behavioral Neuroscience, 2014)
This paper presents a novel rodent decision-making task that explores uncertainty, independently of expectation and predictability. Using a 5-hole operating box, adult male Wistar rats were given choices between a small certain (safe) food reward and a large uncertain (risk) food reward. We found that animals strongly preferred the safe option when it had a fixed position or was cued with a light in a random placement scheme, but had no preference for safe or risk options when the latter were associated with light. Importantly, when the reward was manipulated animals could perceive alterations in the outcome value and biased their choice pattern to the most profitable option. In addition, we found that the D2/D3 agonist quinpirole biased all decisions towards risk in this paradigm. Finally, a c-fos analysis revealed that several brain areas known to be involved in decision-making mechanisms, including the medial prefrontal cortex, the orbitofrontal cortex, the nucleus accumbens and the striatum, were activated by the task. In summary, this paradigm is a useful and highly reliable tool to explore decision-making processes in contexts of uncertainty.